2020
DOI: 10.1016/j.oooo.2020.03.049
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative analysis of metal artifact reduction algorithm performance in volume correction with 3 CBCT devices

Abstract: Objective. The aim of this study was to quantitatively assess the performance of metal artifact reduction (MAR) algorithms on the volume of metal cylinders, considering the influence of materials, positions, and fields of view (FOVs), by using 3 cone beam computed tomography (CBCT) devices (NewTom VGi evo, Picasso Trio, and ProMax 3-D Max). Study Design. Nine phantoms containing cylinders of amalgam, copperÀaluminum (CuAl) metal alloy, and titanium, combined in up to 3 positions, were scanned by using 2 differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Activation of the MAR algorithm, i.e., iterative reconstruction methods that allow reducing image interference is caused by metals or high-density objects by increasing the CNR [ 11 , 31 , 33 ]. The efficacy of MAR depends on the manufacturer of the radiographic machine [ 34 ]. In one study, cylinders made of titanium (Ti) and chromocobalt alloy (CrCo) were exposed to two CBCT devices: Picasso Trio (Vatech, South Korea) and ProMax (Planmeca, Helsinki, Finland).…”
Section: Reviewmentioning
confidence: 99%
“…Activation of the MAR algorithm, i.e., iterative reconstruction methods that allow reducing image interference is caused by metals or high-density objects by increasing the CNR [ 11 , 31 , 33 ]. The efficacy of MAR depends on the manufacturer of the radiographic machine [ 34 ]. In one study, cylinders made of titanium (Ti) and chromocobalt alloy (CrCo) were exposed to two CBCT devices: Picasso Trio (Vatech, South Korea) and ProMax (Planmeca, Helsinki, Finland).…”
Section: Reviewmentioning
confidence: 99%
“…A previous study reported no significant effect of MAR on grey values in the vicinity of dental implants (Parsa et al, 2014). Other investigations found a decrease in artefacts depending on CBCT equipment and material (De Faria Vasconcelos et al, 2020;Mancini et al, 2021). It is worth mentioning that studies in literature have mainly focused on evaluating image quality through quantitative methods.…”
Section: Introductionmentioning
confidence: 96%
“…Artefact generation has been studied and related to the CBCT unit (Freitas et al, 2018;Vasconcelos et al, 2019;De Faria Vasconcelos et al, 2020), artefact-generating material (Queiroz et al, 2018;Vasconcelos et al, 2019;De Faria Vasconcelos et al, 2020;Mancini et al, 2021), positioning (Vasconcelos et al, 2019) and scanning protocol (Freitas et al, 2018;Khosravifard et al, 2021;Mancini et al, 2021;Vasconcelos et al, 2019). To limit the effects of metal artefacts, algorithms for metal artefact reduction (MAR) were developed.…”
Section: Introductionmentioning
confidence: 99%
“…gutta‐percha, metal posts and crowns, and dental implants) (Fontenele et al, 2018; Gaêta‐Araujo et al, 2020). These artifacts include streaking, beam hardening, scatter, photon starvation, and blooming or volumetric distortion (Coelho‐Silva et al, 2021; de Faria Vasconcelos et al, 2020; Schulze et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…De Faria Vasconcelos et al (2020) quantitatively assessed the performance of metal artifact reduction (MAR) algorithms on metal cylinders (amalgam, copper‐aluminum [CuAl] alloy, and titanium), considering the influence of material, position, FOVs, and CBCT device (NewTom VGi evo, Picasso Trio, and ProMax 3‐D Max). MAR only had an impact on images containing amalgam and CuAl and only for the NewTom VGi evo and ProMax 3‐D Max scanners.…”
Section: Introductionmentioning
confidence: 99%